Efektivitas Program Peningkatan Kesejahteraan Petani di Kelurahan Sidomulyo Barat Kecamatan Tuah Madani Kota Pekanbaru - Herman, Herman; Kartius, Kartius; Suriani, Lilis; Kurniawan, Andri; Susanto, Anika Okta Anggraini (Indonesian Journal Publisher, 2025)
This study aims to analyse and explain the effectiveness of the Farmer Welfare Improvement Programme in Sidomulyo Barat Village, Tuah Madani District, Pekanbaru City. This study uses a descriptive research type with a qualitative approach. The informants in this study include the Head of the Agriculture and Fisheries Department of Pekanbaru City, the Head of the Agriculture Division and Extension Officer, the Coordinator of the Agricultural Extension Office (BPP) Tampan, the Field Agricultural Extension Officer (PPL) Tampan, and members of the Baskara Jati Farmers' Group. Data was collected through observation, interviews, and documentation. The data analysis technique used was to assess and conclude that the effectiveness of the Farmer Welfare Improvement Programme in Sidomulyo Barat Village, Tuah Madani District, Pekanbaru City, has not been maximised, as farmers perceive the Farmer Welfare Programme as not yet providing sufficient benefits through various activities that can realise and support farmer welfare. There are still limitations regarding land availability, as much of it has been converted for other uses, and some members have not yet been involved in training.